The Role of Human Resources in Facing an Independent Curriculum: Literature Review - Husain Nurisman; Lidya Natalia Sartono; Hanggono Arie Prabowo; Hermanto; Zeinora; Toto Widiarto; Fadjriah Hapsari; Sutina; Dwi Narsih (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
The independent curriculum is a curriculum that adapts to the rapid development of science. An independent curriculum is the answer, and the government is trying to synchronize the needs of industry with education. Teachers as the front guard are the backbone in implementing the independent curriculum. This research is a literature review research. Literature review is carried out by examining various library sources such as books, articles and other online sources that are relevant to the research topic. The process of implementing an independent curriculum still requires strengthening and adjustments. Teachers need adaptation and time so that the independent curriculum is truly realized in theory and practice. Teachers are expected to be able to understand the independent curriculum and continue to develop the curriculum, including the Pancasila Student Profile Strengthening Project (P5), which is cross-disciplinary learning to observe and think about solutions to problems in the surrounding environment.